BlackNurse-SC: A Novel Attack on SDN Controller - Ravi, Nagarathna; Shalinie, S. Mercy (IEEE communications letters, 2021)
Software-Defined Network (SDN) makes the network programmable by offloading the network modules to the controller in the control plane. Though the controller offers several security features, it is susceptible to attacks. In this letter, we introduce a novel attack named BlackNurse against the SDN Controller (BlackNurse-SC). BlackNurse-SC targets to bring down the controller and create a Denial of Service (DoS) to the whole network. The attacker disrupts the controller by sending out false error messages from his bots. BlackNurse-SC has two salient features. First, the attacker need not generate a flood of malicious packets, thus making it difficult for the controller to detect that it is subject to attack. Second, the attacker poisons the network topology view, which leads to improper functioning of the controller. We launch the attack in our SDN testbed to ascertain the effects it can create in the network. BlackNurse-SC brought down the controller within 20 seconds.